The effect of temperature and viscoelasticity on cavitation dynamics during ultrasonic ablation. - Webb, I; Payne, S; Coussios, C (2011)
Inertial cavitation has been shown to enhance heating rates during high intensity focused ultrasound treatments. Cavitation dynamics will be affected by heating and by the changes in mechanical properties of tissue resultant from thermal denaturation; however, the nature of the change is not known and forms the focus of the current study. A Keller-Miksis equation is used to find the variation in inertial cavitation threshold with temperature in water and, when coupled with a Kelvin-Voigt viscoelastic model, in biological tissue. Simulated thermal ablation treatments in liver and muscle are used to explore the changes in cavitation dynamics, and the resultant frequency spectra of secondary acoustic emissions, due to tissue denaturation. Results indicate that viscosity is the key parameter controlling cavitation dynamics in biological tissues. The increase in viscosity during denaturation is predicted to increase inertial cavitation thresholds, leading to a substantial decrease in the higher harmonic content of the emitted pressure signal across a wide range of bubble radii. Experimental validation of these observations could offer improved methods to monitor therapeutic ultrasound treatments.